Beiträge zur Insektenfauna der DDR: Hymenoptera - Bestimmungstabellen bis zu den Unterfamilien. - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Surveys of the insect fauna of the GDR to be made in the near future will cover only a few groups of the Hymenoptera. As the currently used nomenclature and broad systematology by Schmiedeknecht is no longer adequate to our present knowledge, the author has prepared keys of the superfamilies, families and subfamilies, though the broad systematology of some groups is still very unsatisfactory. The subfamilies and in some cases the families have been chosen as the lowest category because they often have common biological criteria which furnish further characteristics and clues. Subtle distinctions have been deliberately excluded in order to facilitate the use. The keys are meant chiefly as aids and guides for the amateur entomologist, the student or the technical assistant and are not primarily intended for the specialist.